2020
DOI: 10.3389/fnut.2020.606398
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, Vitamin D and Vitamin C: Perspectives for COVID-19 With a Focus on Physical Tissue Barrier Integrity

Abstract: Some nutrients play key roles in maintaining the integrity and function of the immune system, presenting synergistic actions in steps determinant for the immune response. Among these elements, zinc and vitamins C and D stand out for having immunomodulatory functions and for playing roles in preserving physical tissue barriers. Considering the COVID-19 pandemic, nutrients that can optimize the immune system to prevent or lower the risk of severe progression and prognosis of this viral infection become relevant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 192 publications
(271 reference statements)
1
70
0
10
Order By: Relevance
“…Similar conclusions have been also drawn in various recent reviews aimed at assessing the potential positive role of zinc in COVID-19 treatment ( Joachimiak, 2021 ; Celik et al, 2020; de Almeida Brasiel, 2020; Name et al, 2020 ; Pormohammad et al, 2021 ; Rahman and Idi, 2020). In another recent review on the role of nutritional supplements as potential therapeutic adjuvants in COVID-19, Costagliola et al (2021) concluded that the supplementation of vitamin D, probiotics, lactoferrin and zinc, might be useful as an adjuvant treatment in COVID-19, as well as in the prevention of viral spreading.…”
Section: Essential Trace Elements and Covid-19supporting
confidence: 77%
“…Similar conclusions have been also drawn in various recent reviews aimed at assessing the potential positive role of zinc in COVID-19 treatment ( Joachimiak, 2021 ; Celik et al, 2020; de Almeida Brasiel, 2020; Name et al, 2020 ; Pormohammad et al, 2021 ; Rahman and Idi, 2020). In another recent review on the role of nutritional supplements as potential therapeutic adjuvants in COVID-19, Costagliola et al (2021) concluded that the supplementation of vitamin D, probiotics, lactoferrin and zinc, might be useful as an adjuvant treatment in COVID-19, as well as in the prevention of viral spreading.…”
Section: Essential Trace Elements and Covid-19supporting
confidence: 77%
“…[177][178][179] Many individuals globally consume zinc tablets, vitamin C, and B because of immune booster effects and combating COVID-19 and its antiviral. 180,181 However, a recent pre-print United States-based retrospective analysis utilizing electronic medical records found that patients treated with hydroxychloroquine and azithromycin with the addition of zinc sulfate had a higher recovery rate. 182 Interestingly, additional input of zinc sulfate was claimed to be associated with lower mortality rate, need for hospice care, and less invasive ventilation requirements.…”
Section: Evidence Of Zinc's Effectivity On Covid-19 Toxicity and Prmentioning
confidence: 99%
“…Several reports have highlighted the potential role of nutrients in the modulation of the immune response to SARS-CoV-2 or a direct anti-viral and/or anti-SARS-CoV-2 properties[ 50 - 53 ]. During this pandemic, nutritional aspects such as obesity[ 7 , 54 ], malnutrition[ 55 ], and micronutrient deficiency[ 56 , 57 ] have been postulated as risk factors for severe COVID-19. Nevertheless, the composition of the human microbiota is influenced by many factors, including dietary components[ 41 ].…”
Section: Nutritional Interventionmentioning
confidence: 99%